A Study of Some Economic Indicators of Hulling and Bleaching Machines on the Cultivar of Rice,Tarm Hashemi (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present experiment has been conducted to evaluate of some economic indicators of hulling and bleaching machines of cultivar rice, Tarm Hashemi in the laboratories of the University of Tehran to 2015. Research has included use of two types of machines Satake and Yanmar, under three levels of a moisture content of grain, 10-12 %, 12- 14% and 14-16%), and three levels of clearance between cylinders 0.4, 0.6 and 0.8 mm. The results indicated that the machine type Satake is significantly better on the machine type Yanmar in all studies factors. When increase grain moisture content leads to an increase in the costs, while when increase clearance among cylinder leads to a decrease the costs to all studied traits. The overlap between the machine type Satake and moisture content of grain  10-12%  is superior significantly and also overlap between the machine type Satake to clearance 0.8. in all studied factors as compared with the machine type Yanmar with a moisture content of grain and two clearance 0.4 mm in all studied factors. The best results have come from the triple overlap among machine type Satake, grain moisture 10-12%, and clearance 0.8 mm in all studies factors.